Theoretical investigations of two-dimensional intrinsic magnets derived from transition-metal borides M3B4 (M = Cr, Mn, and Fe) - Chunmei Ma; Shiyao Wang; Chenguang Gao; Junjie Wang (Science and Technology of Advanced Materials)
Two-dimensional (2D) magnetic materials with high critical temperatures (TC) and robust magnetic anisotropy energies (MAE) hold significant potential for spintronic applications. However, most of 2D magnetic materials are derived from the van der Waals (vdW) layered bulks, which greatly limits the synthesis of 2D magnetic materials. Here, 2D M3B4 (M = Cr, Mn, and Fe; B = Boron), derived from hexagonal and orthorhombic M3AlB4 phases by selectively etching Al layers, was studied for its structural stability, electronic structure, and magnetic properties. By utilizing ab initio calculations and Monte Carlo simulations, we found that the orthorhombic Cr3B4 shows ferromagnetic (FM) metal and possesses an in-plane magnetic easy axis, while the remaining hexagonal and orthorhombic M3B4 structures exhibit antiferromagnetic (AFM) metals with a magnetic easy axis which is perpendicular to the two-dimensional plane. The critical temperatures of these 2D M3B4 structures are found to be above the 130 K. Notably, the ort-Mn3B4 possesses highest TC (~600 K) and strongest MAE (~220 µeV/atom) among these borides-based 2D magnetic materials. Our findings reveal that the 2D M3B4 compounds exhibit much better resistance to deformation compared to M2B2 MBenes and other 2D magnetic materials. The combination of high critical temperature, robust MAE, and excellent mechanical properties makes 2D Mn3B4 monolayer exhibits a favorable potential for spintronic applications. Our research also sheds light on the magnetic coupling mechanism of 2D M3B4, providing valuable insights into its fundamental characteristics.